2016
DOI: 10.1016/j.ssmph.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes in bereaved mothers: The importance of household income and education

Abstract: Intense and enduring psychological distress has been well-documented in numerous studies on bereaved parents including anxious, depressive, and traumatic stress symptoms. A state of poverty is also known to increase the risk of psychological distress in the general population, yet this variable has not yet been sufficiently evaluated in outcomes specifically for bereaved parents. This study is the first to investigate poverty, education, and parental bereavement while examining the relative risk of other varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…First, the association between low household income and CG symptoms demonstrates the importance of low income as a potential risk factor in the development and persistence of CG. This association complements the study of Cacciatore et al (2016), which demonstrated a correlation between poverty and grief-related symptoms of depression and PTSD in bereaved parents. In the present analysis, these findings are extended to a bereavement-specific outcome variable (CG), among a more heterogeneous sample of helpseeking bereaved adults.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…First, the association between low household income and CG symptoms demonstrates the importance of low income as a potential risk factor in the development and persistence of CG. This association complements the study of Cacciatore et al (2016), which demonstrated a correlation between poverty and grief-related symptoms of depression and PTSD in bereaved parents. In the present analysis, these findings are extended to a bereavement-specific outcome variable (CG), among a more heterogeneous sample of helpseeking bereaved adults.…”
Section: Discussionsupporting
confidence: 80%
“…Second, following indications from Cacciatore et al (2016) that income is a strong predictor of loss-related depression, anxiety, and posttraumatic stress symptoms, we examined the association between income and grief levels among helpseeking bereaved adults. We expected to find a strong effect of poverty on CG symptoms even compared to other recognized predictors of CG, including cause of death and gender.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Finally, mothers who lost a child to death were generally older, lived in neighbourhoods of higher socioeconomic status, and were less likely to have received welfare before the loss of their child (see Table 1); these mothers may be better resourced to access support outside of the public health system following their loss. 30,31 The population-based repository at the Manitoba Centre for Health Policy has some significant strengths, such as a large sample size, minimal attrition, and numerous predictors over many years. The use of linkable administrative data also minimised the risk of surveillance bias, as the data were collected independently of the research hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…11 Bereaved parents also experience psychological distress such as anxiety, post-traumatic stress disorder, and grief-related depressive symptoms that continue to be significant for years after a child's death. 8,12,13 In addition to the physical health of parents, the death of a child can affect social relationships. Bereaved parents report decreased communication, feelings of isolation, an absence of close social relationships, and increased marital strain and divorce.…”
Section: Introductionmentioning
confidence: 99%